Implementation of special program of pajale (rice, corn and soybean) in terara district, east lombok regency - Sari, Makdis; Sjah, Taslim (International research journal of management, IT and social sciences, 2016)
The government of Indonesia has targeted self-sufficiency in production of rice, maize, and soybean in a program called “Upsus Pajale” (Special effort for increasing production of rice, maize, and soybean). This paper aims to describe the implementation of “Pajale” program by farmers, problem, and kinds of actives in the program. The result of this study reveals that there was an improvement in the production of rice, yet there were problems at both farmers and extensions worker. Recommendation for this study is that supervision needs to be a beginner at the start of the season for better duty implementation, and a supervisor’s salary needs to be increased for improving working motivation.